Early mobilization of patients with subarachnoid haemorrhage: a national survey of french intensive care units - Adéla Foudhaili; Damien Vitiello; Benjamin Glenn Chosuterman (Journal of Rehabilitation Medicine, 2024)
Objective: To describe French intensive care unit practices regarding the mobilization of patients with subarachnoid haemorrhage.